Regional head leadership relations model in the perspective of power in Deli Serdang Regency, Indonesia - Rajekshah, Musa; Subhilhar, Subhilhar; Kusmanto, Heri; Ridho, Hatta (Research Journal in Advanced Humanities, 2023)
This study aims to explain the Regional Head Leadership Model from the perspective of power in Deli Serdang Regency. The leadership style greatly influences the structure under it, both in terms of political party institutions and internal bureaucratic institutions. The leadership in Deli Serdang Regency comes from the same family but has different character; this also gives the uniqueness of the leadership relationship model that is carried out. This study used a phenomenological descriptive-analytical method with a qualitative approach. The results show that leadership and background factors strongly influence the relationship model. The characteristics of leader such as Ashari Tambunan who come from civil society are considered more populist considering the conditions in Deli Serdang Regency where the people are very diverse. So, the civilians are more flexible because they come from civil society, while the leadership model of the late Amri Tambunan, who came from bureaucrats, is synonymous with firmness and calmness in making decisions. The application of a combination of leadership types maintains its power in Deli Serdang Regency. The power that is exercised in Deli Serdang Regency has approaches of kinship, humanism and mutual cooperation in developing Deli Serdang Regency.